2009
DOI: 10.1093/tropej/fmp036
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Ghrelin, Tumor Necrosis Factor-  and Interleukin-6 in Infants and Children with Congenital Heart Disease

Abstract: Serum ghrelin, TNF-alpha and IL-6 levels are elevated in patients with CHD whether acyanotic or cyanotic. Increased ghrelin levels represent malnutrition and growth retardation in these patients. The relation of ghrelin with TNF-alpha may be explained by the possible effect of chronic congestive heart failure and chronic shunt hypoxemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
3
21
1
3
Order By: Relevance
“…IL-6 can also be upregulated and released from renal tubular epithelial cells in response to injury and plays a fundamental role in the pathophysiology of AKI [32]. Additionally, IL-6 production is increased by the myocardium in states of congestive heart failure, cardiac ischemia, and congenital heart disease [33-35]. Preoperatively, we found that IL-6 was statistically different in patients who did and did not go on to develop stage 2/3 AKI.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 can also be upregulated and released from renal tubular epithelial cells in response to injury and plays a fundamental role in the pathophysiology of AKI [32]. Additionally, IL-6 production is increased by the myocardium in states of congestive heart failure, cardiac ischemia, and congenital heart disease [33-35]. Preoperatively, we found that IL-6 was statistically different in patients who did and did not go on to develop stage 2/3 AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Açlık hormonu olarak bilinen ghrelin, malnütrisyon ve büyüme geriliğindeki enerji metabolizmasındaki eksikliği dengelemek üzere artar. Doğuştan kalp hastalığı olan çocuklarda serum ghrelin düzeylerinin yüksek olduğu ve ghrelin düzeyleri ile VKİ arasında negatif ilişki olduğu gösterilmiştir (31,32). Sık geçirilen enfeksiyonlar DKH'lı çocuklardaki büyüme geriliği ve malnütrisyon gelişiminin en önemli nedenlerinden birisidir (6,28).…”
Section: Discussionunclassified
“…(33) yaptıkları çalışmalarında malnütrisyonun konjestif kalp yetmezliği ve siyanozu olan hastalarda belirgin olduğunu bildirmektedir. Doğuştan kalp hastalığı olan çocuklarda TNF-alfa ve IL-6 seviyelerinin yüksek olduğu gösterilmiştir (31). Serum ghrelin düzeylerinin asiyanotik DKH olanlarda siyanotik DKH olanlardan daha yüksek olması ve serum ghrelin düzeyleri ile TNF-alfa düzeyleri arasındaki pozitif ilişkinin saptanması; malnütrisyonun konjestif kalp yetmezliği ve kronik hipoksi ile ilişkili olduğunu desteklemektedir (31).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Recently, researchers found that total plasma ghrelin levels were elevated in adult patients with idiopathic pulmonary arterial hypertension, and increased plasma ghrelin levels correlated positively with pulmonary artery systolic pressure (PASP) and nitric oxide (NO) [40]. Although total plasma ghrelin levels were higher in children with CHD [1,18,42], none of the study subjects had PH. In addition, the acylated ghrelin which possesses biological activity has not been investigated in children with PH-CHD.…”
Section: Introductionmentioning
confidence: 99%